Cross-chain medical data sharing scheme based on elliptic curve signcryption - YU Huifang; LI Lei (Tongxin xuebao)
Decentralized blockchain can realize the storage of medical data. Due to high isolation of blockchain from external environments, medical data in inside blockchain of medical institutions can only be shared within institution itself. To address the requester identity authentication and shared data security in cross-chain medical data sharing, a cross- chain medical data sharing scheme based on elliptic curve signcryption was devised in this article. Relay chain was used to realize interactive sharing of medical data. Cross-chain medical data was hierarchically processed for better effect of cross-chain data exchange. Signcryption process was completed by smart contracts to obtain high execution efficiency. Deletion and modification functions of medical data were deployed in smart contracts to solve the frequent updation problem of medical data.